Scepticism about the virtue ethics approach to nursing ethics - Holland, Stephen (Nursing philosophy, 2010)
Nursing ethics centres on how nurses ought to respond to the moral situations that arise in their professional contexts. Nursing ethicists invoke normative approaches from moral philosophy. Specifically, it is increasingly common for nursing ethicists to apply virtue ethics to moral problems encountered by nurses. The point of this article is to argue for scepticism about this approach. First, the research question is motivated by showing that requirements on nurses such as to be kind, do not suffice to establish virtue ethics in nursing because normative rivals (such as utilitarians) can say as much; and the teleology distinctive of virtue ethics does not transpose to a professional context, such as nursing. Next, scepticism is argued for by responding to various attempts to secure a role for virtue ethics in nursing. The upshot is that virtue ethics is best left where it belongs - in personal moral life, not professional ethics - and nursing ethics is best done by taking other approaches.